Protein‐Nanocaged Selenium Induces t(8;21) Leukemia Cell Differentiation via Epigenetic Regulation - Long Fang; Ruofei Zhang; Lin Shi; Jiaying Xie; Long Ma; Yili Yang; Xiyun Yan; Kelong Fan (Advanced Science, 2023)
Abstract The success of arsenic in degrading PML‐RARα oncoprotein illustrates the great anti‐leukemia value of inorganics. Inspired by this, the therapeutic effect of inorganic selenium on t(8; 21) leukemia is studied, which has shown promising anti‐cancer effects on solid tumors. A leukemia‐targeting selenium nanomedicine is rationally built with bioengineered protein nanocage and is demonstrated to be an effective epigenetic drug for inducing the differentiation of t(8;21) leukemia. The selenium drug significantly induces the differentiation of t(8;21) leukemia cells into more mature myeloid cells. Mechanistic analysis shows that the selenium is metabolized into bioactive forms in cells, which drives the degradation of the AML1‐ETO oncoprotein by inhibiting histone deacetylases activity, resulting in the regulation of AML1‐ETO target genes. The regulation results in a significant increase in the expression levels of myeloid differentiation transcription factors PU.1 and C/EBPα, and a significant decrease in the expression level of C‐KIT protein, a member of the type III receptor tyrosine kinase family. This study demonstrates that this protein‐nanocaged selenium is a potential therapeutic drug against t(8;21) leukemia through epigenetic regulation.